IDENTIFICATION AND BIOLOGICAL ACTIVITY TEST SOME ISOLATED COMPOUNDS FROM STEM BARK OF MELINJO (GNETUM GNEMON) - Atun, Sri; Arianingrum, Retno; Masatake, Niwa (Jurnal Sains Dasar, 2012)
Isolation and structure elucidation of two compounds, namely resveratrol (1), and 3- methoxyresveratrol (2) from stem bark of Melinjo (Gnetum gnemon) had been done. The isolation of those compounds was carried out by chromatographyc method and structure elucidation was performed by interpretation of spectroscopic data, including UV, IR,  1H and 13C NMR 1D and 2D, and FABMS. The result of this study showed that activity each compounds as radical hydroxyl scavenger of resveratrol (1), and 3-methoxyresveratrol (2), with an  IC50 45,17 and 60,12; g/ml respectively. Each compound showed significant activity as UV-B protection. Activity test as UV-B protection showed that resveratrol and methoxyresveratrol have maximum protections (SPF 8,03 and 12,34 respectively), each compounds on 50 g/ml. Key word : melinjo; Gnetum gnemon; natural antioxidant; UV-B protection